2021
DOI: 10.1108/ijopm-07-2020-0484
|View full text |Cite
|
Sign up to set email alerts
|

Do network capabilities improve corporate financial performance? Evidence from financial supply chains

Abstract: PurposeThe purpose of this study is to bridge the gap in the literature on supply chain finance (SCF) by exploring the relationship between network capabilities and corporate financial performance (CFP) in financial supply chains (FSCs).Design/methodology/approachThe authors collect panel data and adopt regression analysis to analyse the joint investment activities among 1359 manufacturing firms and 289 financial service providers in China to explore how network capabilities, both network power and network cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…(2018) found that a moderate scope of control creates higher supply network performance. Focusing on financial supply chain networks, Wang et al . (2021) found that a focal firm's network centrality increases its financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) found that a moderate scope of control creates higher supply network performance. Focusing on financial supply chain networks, Wang et al . (2021) found that a focal firm's network centrality increases its financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Developing an NK model of the supply network, Giannoccaro et al (2018) found that a moderate scope of control creates higher supply network performance. Focusing on financial supply chain networks, Wang et al (2021) found that a focal firm's network centrality increases its financial performance. Studying supply chain disruption caused by 2011 Tohoku earthquake, Son et al (2021) found that affected companies have lower indegree and outdegree centralities (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research findings revealed that SCC plays a mediator role in the relation between SCI and SCP (Morash, 2001; Mandal, 2017; Wang et al , 2021). This finding coincides with Morash (2001), who proposed that when SCI and SCC increase, SCC effectively meets the strategic objectives of the enterprise and improves SCP.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The SCI acquired belongs to collaboration and cooperation are featured as a valued supply chain resource (Irfan and Wang, 2019; Dobrucalı, 2020; Ataseven et al , 2020). This study proposes a conceptual model that valuable resource of SSI (resource input) is transferred into SCC and build SCP by integrated capability and spread to other units of the business-to-business network cooperation through DI as a mediation role (resource output) (Mandal, 2017; Wang et al , 2021). The supply chain management thereby focuses on the specific role of DI with the influence on SCC and SCP (Rajaguru and Matanda, 2019; Irfan and Wang, 2019; Han and Huo, 2020; Ganbold et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by Piotroski (2000) and Wang et al. (2021a, b), we try to use listed companies to symbolise the industry in a certain city as a whole because they are the major participants in the city, such that we can use the market value of these listed firms as indicators to forecast the performance of the smart city industry. Asgharian et al.…”
Section: Introductionmentioning
confidence: 99%